BUSINESS STRATEGY, RESOURCES AND CAPABILITIES AND ORGANISATIONAL INNOVATION PERFORMANCE - Mohamed, Rapiah; Jamil, Che Zuriana Muhammad; Mutalib, Hafizah Abd (CENTRAL ASIA AND THE CAUCASUS, 2021)
The survival of small and medium enterprises (SMEs) is crucial for Malaysian economic growth and employment opportunity. Innovation is a strategic weapon to compete in the market. The intense competition requires SMEs to continue searching for new ideas and innovate. However, the innovation performance of SMEs is at a low level. This could hinder SMEs to maintain customers and increase their business profitability. Hence, the objective of this paper is to examine the factors that influence innovation performance. Specifically, this paper investigates the influence of business strategy on innovation performance indirectly through organisational resources and capabilities. The framework of this study is based on the Resource-based View theory. A total of 40 samples of SMEs in the manufacturing sector were collected and used for data analysis. The data were analysed using SmartPLS 3.3.3 version. The findings confirmed the hypothesis that organisational resources and capabilities have a mediating effect in the relationship between business strategy and innovation performance. The findings agree with the Resource-based View theory on the importance of resources and capabilities as a source for competitive advantage. Further, the results provide SME managers and policymakers the importance of understanding the role of business strategy, resources, and capabilities to improve innovation performance.